Perubahan Karakter Tokoh Dalam Cerpen Malin Kundang Karya Sapardi Djoko Damono Dan Naskah Drama Malin Karya M. S Nugroho: Change Of Character In “Malin Kundang” Short Story By Sapardi Djoko Damono And “Malin” Drama Text By M. S Nugroho - Vena Silviana; Eris Septiani; Rizki Ramadhan (Balai Bahasa Provinsi Papua, 2022)
Malin Kundang is one of the famous legends from the province of West Sumatra. His disobedient character to his mother made him have to experience the curse that his mother gave him. In this study, the researcher will discuss about the characters in the short story Malin Kundang in kumcer On One Day by Sapardi Djoko Damono by comparing the characters in the drama script Malin by W.S Nugroho. So that it can be found differences in the characters of the two literary works. The method used in this research is descriptive qualitative. The results of this study are that there are differences in the character of the characters that can be seen clearly and the addition of characters in the M.S Nugroho drama script.